2016
DOI: 10.1038/srep20686
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing Flow Cytometry Immunophenotyping Analysis from the Human ImmunoPhenotyping Consortium

Abstract: Standardization of immunophenotyping requires careful attention to reagents, sample handling, instrument setup, and data analysis, and is essential for successful cross-study and cross-center comparison of data. Experts developed five standardized, eight-color panels for identification of major immune cell subsets in peripheral blood. These were produced as pre-configured, lyophilized, reagents in 96-well plates. We present the results of a coordinated analysis of samples across nine laboratories using these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
243
0
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(253 citation statements)
references
References 29 publications
6
243
0
4
Order By: Relevance
“…A reference dataset is constructed and new samples, analysed with the same panels, can be mapped onto this reference to classify a patient. Also in larger community-wide efforts, such as the Human Immunology Project Consortium (HIPC) 25 or the Milieu Interieur project 26 , the design of standardized panels is of key importance. To facilitate sharing and dissemination of optimized panels, the cytometry community has recently introduced a new series of protocols to improve reproducibility, referred to as optimized multicolour immunofluorescence panels (OMIPs) 27 .…”
Section: Standardization and Reproducibilitymentioning
confidence: 99%
“…A reference dataset is constructed and new samples, analysed with the same panels, can be mapped onto this reference to classify a patient. Also in larger community-wide efforts, such as the Human Immunology Project Consortium (HIPC) 25 or the Milieu Interieur project 26 , the design of standardized panels is of key importance. To facilitate sharing and dissemination of optimized panels, the cytometry community has recently introduced a new series of protocols to improve reproducibility, referred to as optimized multicolour immunofluorescence panels (OMIPs) 27 .…”
Section: Standardization and Reproducibilitymentioning
confidence: 99%
“…Transformation and compensation were done using the preprocessing.batch function in MetaCyto (Hu et al, 2017). The cell definitions from the Human ImmunoPhenotyping Consortium (Finak et al, 2016) were used to identify 24 types of immune cells using the searchClster.batch function in MetaCyto. Specifically, each marker in each cytometry panels was bisected into positive and negative regions.…”
Section: Star⋆methodsmentioning
confidence: 99%
“…A reference “immunome” might reasonably include flow cytometry, gene expression, human leukocyte antigen (HLA) type, cytokine measurements, clinical assessments, and more. Furthermore, standardized protocols for measurement and conventions for naming cell types and cytokines are only currently being developed, and adherence is inconsistent (Finak et al., 2016). For the experimental or clinical immunologist, the cost of generating the necessary data from scratch—or the temporal and computational costs associated with standardizing and harmonizing data from publicly available cohorts across platforms, time points, and institutions—is prohibitive without significant resources.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Finak et al [19] reported that in multi-centric studies the intra-site variability is generally low, but the inter-site variability is a major problem, which also was confirmed by others [18,20,127]. This predominantly was due to unintended deviations in preparation and analyses between the different sites even though detailed SOPs (standard operating procedures) were provided [19].…”
Section: Discussionmentioning
confidence: 86%